Piano sonata no. 8 in C minor, op. 13, edited by Bennett and Macfarren - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Bennett, William Sterndale, 1816-1875 (editor):::Contributor::::::::::::; Macfarren, Walter, 1826-1905 (editor):::Contributor:::::::::::: (London; United Kingdom; Edwin Ashdown, 2024)
Edition of the Piano Sonata no. 8 in C minor, op. 13 (Pathètique) from "Sir William Sterndale Bennett's Edition of Beethoven's Sonatas for the Pianoforte," with revisions and fingerings by Walter Macfarren, published by Edwin Ashdown in London.